Aidi Injection as Adjuvant Drug Combined with Chemotherapy in Treatment of Breast Cancer: A Systematic Meta-Analysis. (8th January 2021) - Wu, Chenhao; Qi, Yongjun; Zhou, Juan; Yao, Chen; Miao, Min; Cheng, Chen
Abstract : Objective . To compare the efficacy and safety of combination of Aidi injection and chemotherapy and chemotherapy alone in treatment of breast cancer. Methods . The related control and randomized studies till August 1 st, 2020, were retrieved in the database including PubMed, Embase, Cochrane Library, CNKI, CBM, Wang-Fang, and VIP. Primary outcomes were response rate (RR) and performance status (KPS) improvement rate; secondary outcomes were rate of adverse drug reactions (ADR) including myelosuppression, digestive tract reaction, liver dysfunction, and cardiac toxicity. Review Manager 5.3 was used in the present analysis. Results . In total, 20 studies (18 articles) were included in the present analysis. RR (OR 1.76 (1.32, 2.35); p = 0.0001 ) and KPS improvement rate (OR: 2.68 (1.34, 6.46); p = 0.007 ) in Aidi injection plus chemotherapy group were significantly higher than those of chemotherapy alone group. Addition of Aidi injection significantly reduced the rate of myelosuppression, digestive tract reaction, leukocyte decrease, II-IV cardiac function abnormality, atrial dysrhythmia, ventricular arrhythmia, ST segment T wave inversion, and abnormal ECG (all p < 0.05 ). Conclusion . Aidi injection could increase the efficacy of chemotherapy, could reduce myelosuppression, digestive tract reaction, and cardiac toxicity induced by chemotherapy, and did not lead to additional toxicity and side effect. Therefore, it is an anticancer drug with good efficacy and low toxicity, worth further popularization.